Electrodeposited Nanostructured CoFe2O4 for Overall Water Splitting and Supercapacitor Applications - Zhang, Chunyang; Bhoyate, Sanket; Zhao, Chen; Kahol, Pawan K.; Kostoglou, Nikolaos; Mitterer, Christian; Hinder, Steven J.; Baker, Mark A.; Constantinides, Georgios; Polychronopoulou, Kyriaki; Rebholz, Claus; Gupta, Ram K. (My University, 2019)
To contribute to solving global energy problems, a multifunctional CoFe 2 O 4 spinel was synthesized and used as a catalyst for overall water splitting and as an electrode material for supercapacitors. The ultra-fast one-step electrodeposition of CoFe 2 O 4 over conducting substrates provides an economic pathway to high-performance energy devices. Electrodeposited CoFe 2 O 4 on Ni-foam showed a low overpotential of 270 mV and a Tafel slope of 31 mV/dec. The results indicated a higher conductivity for electrodeposited compared with dip-coated CoFe 2 O 4 with enhanced device performance. Moreover, bending and chronoamperometry studies suggest excellent durability of the catalytic electrode for long-term use. The energy storage behavior of CoFe 2 O 4 showed high specific capacitance of 768 F/g at a current density of 0.5 A/g and maintained about 80% retention after 10,000 cycles. These results demonstrate the competitiveness and multifunctional applicability of the CoFe 2 O 4 spinel to be used for energy generation and storage devices.
Keywords: CoFeO 24; HER; OER; Overall water splitting; Supercapacitor